PENGARUH KUALITAS PRODUK, HARGA, PROMOSI, DAN DISTRIBUSI TERHADAP MINAT BELI KONSUMEN TOKO VIZCAKE PEKANBARU - Nabilatul Abda; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was conducted in a new VizCake store located in Jalan JendralSudirman No. 418 Pekanbaru. The problem in this research is not achieving company’ssales target in the last five years and the percentage of achievement of sales targetdecrease in three consecutive years and the least increase of buyer number, this isallegedly influenced by consumer buying interest. The purpose of this study is todetermine the effect of product quality, price, promotion, and distribution of new VizCakestore.In this research the method used is descriptive quantitative by using SPSSprogram. Population in this study are consumers who buy VizCake products thatamounted to 31,879 consumers. Samples taken based on menthod using slovin formulathat is 100 responden and menthod of collecting data using questioner.This study aims to determine how much influence the quality of products, price,promotion, and distribution of consumer buying interest. Technique used AccidentalSampling, data obtained by using simple regression analysis and multiple regressionanalysis. The results of this study indicate product quality, price, promotion, anddistribution have a positive and significant impact on consumer buying interest.Keywords : product quality, price, promotion, distribution, and consumer buyinginterest.